Adaptive Psychosocial Competencies: Toward a Development of a Framework for Life Skills-Based Philippine Nursing Education Curricula - Sali, Abdul Haiy A. (International Journal of Social Learning (IJSL), 2023)
In the Philippines, the nursing curriculum has a solid liberal arts and sciences education with a transdisciplinary approach. In their formative years, the most common source of stress for student nurses was related to academics. However, countries around the world formalize initiatives on life skills education to promote adaptive psychosocial skills and abilities to achieve holistic development. The study aimed to explore and examine the Bachelor of Science in Nursing program and its implications for life skills education in the curricula. This study employed a qualitative research design, mainly through needs analysis, literature review, and theoretical synthesis. The investigation revealed that the academic rigor and practice of the nursing program influenced students’ ability to cope with stress. The full nursing curriculum is considered eclectic; however, life skills competency integration needs to be more obscure. The nursing curriculum must have a striking balance of cognitive, psychomotor, and affective domains. Furthermore, life skills education in nursing must uphold caring as the core value proposed in the Humanistic Life Skills Framework for Nursing. Life skills education should be strengthened, which is imperative in the current nursing program.